Sustainable intensification of agriculture - the role of birds, bees and trees - Uganda Wildlife Authority (Cambridge Conservation Initiative, 2008)
Uganda’s population is now above 34.5 million up from about 16 million in the 1991 (UBOS, 2002). The country’s size and in particular arable land upon which people depend however remain constant and is seriously undergoing degradation. Increasing land productivity yet conserving biodiversity is a challenge Uganda has to meet to secure survival and wellbeing of its people and also the environment. To help determine approaches that would help enhance productivity per unit area of land while conserving biodiversity and consequently the ecosystem’s ecological integrity and services (natural capital), two studies were conducted in the banana coffee zones(the most densely populated region) of Uganda. This policy brief is based on results from research carried out between 2006 and 2008 under the project “Conserving biodiversity on the modernizing farmed landscapes of Uganda”. The project identified best practices for the long-term conservation of biodiversity in a sample of typical farmed landscapes in Uganda and established a framework for sustainable agricultural development and monitoring. The results can be used to support both policy and technological approaches to protect the environment and provide a basis for sustainable development.